Scandium Aluminium Nitride-Based Film Bulk Acoustic Resonators - Michael Schneider; Mario DeMiguel-Ramos; Andrew J. Flewitt; Enrique Iborra; Ulrich Schmid (Proceedings, 2017)
Film bulk acoustic resonators (FBAR) are promising candidates to replace surface acoustic wave devices as filters or delay lines, but also offer exciting opportunities as biological or gas sensors. In this work, solidly mounted FBARs were manufactured by substituting commonly used pure aluminium nitride (AlN) by scandium doped aluminium nitride (ScAlN) thin films as the piezoelectric layer. The ScAlN-based resonators feature a significant improvement of the electromechanical coupling factor from ~3% to ~12% compared to the pure AlN, while the decreased stiffness of ScAlN results in a decrease of the quality factor from ~300 to ~100 due to increased damping losses in the piezoelectric material.